2016
DOI: 10.1039/c6ta00603e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of moisture on (La, A)MnO3 (A = Ca, Sr, and Ba) solid oxide fuel cell cathodes: a first-principles and experimental study

Abstract: In solid oxide fuel cells (SOFCs), cathode degradation in the presence of moisture is a major concern at higher temperatures. We provide a comprehensive picture of the interaction between moisture and (La, A)MnO3 based SOFC cathodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 66 publications
1
25
0
Order By: Relevance
“…For example, moisture can accelerate SrO segregation on LSM. Sharma et al [241] reported that exposure to 20% moisture enhanced SrO segregation on LSM after annealing at 800 °C for 50 h. Hu et al [242] Kim et al [243] observed La 2 O 3 segregation on LSM surfaces annealed at 800 °C for 5 h in 20% and 40% humidified air that was different as compared with annealing in dry air. Liu et al [197] also reported that exposure to 20% moisture at 800 °C for 200 h led to the partial decomposition of LSM into La 2 O 3 and MnO x .…”
Section: H 2 Omentioning
confidence: 99%
“…For example, moisture can accelerate SrO segregation on LSM. Sharma et al [241] reported that exposure to 20% moisture enhanced SrO segregation on LSM after annealing at 800 °C for 50 h. Hu et al [242] Kim et al [243] observed La 2 O 3 segregation on LSM surfaces annealed at 800 °C for 5 h in 20% and 40% humidified air that was different as compared with annealing in dry air. Liu et al [197] also reported that exposure to 20% moisture at 800 °C for 200 h led to the partial decomposition of LSM into La 2 O 3 and MnO x .…”
Section: H 2 Omentioning
confidence: 99%
“…Moreover, the synergy among multidisciplinary sciences, along with rapid advancements in the electronic-structure methods, computational resources, and experimental techniques has made the process of materials design faster and far more efficient in some cases. As a result, the community is gradually migrating towards systematic computation-driven materials selection paradigms 9,10,[13][14][15][16][17][18][19][28][29][30][31][32][33][34][35] , where functional materials are screened by establishing a direct link between the macroscopic functionality and the atomic-scale nature of the material. We are in a data-rich, modeling-driven era where trial and error approaches are gradually being replaced by rational strategies 9,[36][37][38] , which couple predictions not only from specific electronic-structure calculations of a given property but also by learning from the existing data using machine learning.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the community is gradually migrating towards systematic computation-driven materials selection paradigms, 4,5,[8][9][10][11][12][13][14][21][22][23][24][25][26][27][28][29] where functional materials are screened by establishing a direct link between the macroscopic functionality and the atomic-scale nature of the material. We are in a data-rich, modeling-driven era where trial and error approaches are gradually being replaced by rational strategies, 24,[30][31][32] which couple predictions not only from specific electronicstructure calculations of a given property, but also by learning from the existing data using machine learning.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the oxidation state of manganese and the oxygen vacancy concentration can be regulated by the insertion of an external cation into the LaMnO 3 matrix. For instance, according to first-principles calculations, Sharma et al proved that the surface of Ca-, Sr-, and Ba-substituted LaMnO 3 (A = Ca, Sr, and Ba) was more prone to oxygen vacancies, which further accelerated the segregation of cations and affected the surface chemistry of the cathode material . Hu et al reported La 1– x Ca x MnO 3 perovskite–graphene composites as catalysts and discovered that the composites exhibited the highest electrocatalytic activity with a electron transfer number of 3.6 while the doping content of calcium was equal to x = 0.4 .…”
Section: Introductionmentioning
confidence: 99%